THE EFFECTIVENESS OF INSTAGRAM FILTER TO IMPROVE STUDENTS’ VOCABULARY - Aisyah Noor Auly; Theresia Cicik Shopia Budiman; Faiza Hawa (Journal of English Language Learning, 2021)
Vocabulary becomes an important aspect to learn because it is the tool to recognize words’ meaning and sentences, and to create sentences, paragraphs and texts.  In order to improve students’ vocabularies, media are needed to help students memorize them. The aim of the research is to notice how effective Instagram filter in enhancing students’ vocabulary comprehension. For this reason, teacher should find an innovative media for teaching vocabulary to students in most interesting way. Lately, Instagram becomes the most widely used social networking platform. Most people spend a lot of time scrolling on Instagram just to have fun, find some information, or even to get new friends. This platform is served with feed, stories, reel, IG TV and IG filter. This study employed IG filter to be used as a media to teach vocabulary to students. This is based on what the researchers observed that most students in schools, in this case is high school, like to play with Instagram filters. This what makes the researchers interested in using Instagram filter as a media for teaching vocabularies. This research is designed as quasi experiment which is held in one of senior high schools in Jepara. The findings reveal that IG filter is effective and successful to be used as a media for teaching vocabulary and to improve students’ comprehension in vocabulary. The average score was in good category (86.33). While the N-gain score was 58.72% which is categorized as quite effective. It means that Instagram filters is quite effective as a learning media.